LSX molecular sieve as well as preparation method and application thereof
Through thermal activation, alkali fusion and crystallization reaction, high-purity LSX molecular sieve is prepared using secondary resources, which solves the problems of low purity and poor quality of secondary resource synthesis in the prior art, and achieves cost reduction and industrial production, which is convenient for Sustainable use of the environment and economy.
Patent Information
- Application Number
- CN202310812100.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the purity and poor quality of secondary resource synthesis zeolites have low purity and poor quality, resulting in low efficiency of high value utilization of secondary resources and high production costs, making it difficult to achieve industrial production.
Using thermal activation, alkali fusion and crystallization reaction methods, high-purity LSX molecular sieve is prepared by combining with the first alkali source and the second alkali source, and secondary resources such as rare earth tailings, coal gangue or fly ash are used as Raw materials significantly reduce production costs and simplify process flow to facilitate industrial production.
It realizes the preparation of LSX molecular sieve with high purity and excellent quality, reduces production costs, solves the problem of accumulation of secondary resources, is of great significance to the environment and economy, has simple process, is convenient for industrial production, and improves the ion exchange performance of the product .
Smart Images

Figure CN119263298A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of molecular sieve materials, and in particular relates to an LSX molecular sieve and a preparation method and application thereof. Background Art
[0002] At present, the accumulation of secondary resources such as coal gangue, rare earth tailings, and fly ash is increasing year by year. The management of secondary resources is crucial to the development of my country's society and economy. At present, secondary resources have been widely used in many fields such as underground mine site filling, fertilizer production, and civil engineering. In recent years, secondary resources have also begun to be used in the preparation of high-value products such as ceramics, cement, zeolite, catalysts, glass and other products. High-value utilization of secondary resources will be one of the effective ways to recycle secondary resources.
[0003] Zeolite is composed of [SiO 4 ]、[AlO 4 ] A series of porous materials with a three-dimensional spatial network structure composed of tetrahedrons and exchangeable metal cations, which have been widely used in the fields of gas separation, wastewater treatment, catalysis and antibacterial materials. Since the constituent elements of secondary resources are similar to those of zeolites, synthesizing zeolites using secondary resources as raw materials will be one of the effective ways to utilize secondary resources. For example, CN113307282B discloses a method for synthesizing sodalite zeolite molecular sieves from coal gangue solid waste, using coal gangue solid waste as raw material, activating coal gangue by mechanochemical method, and then synthesizing carbon-containing zeolite molecular sieves from the activated coal gangue by alkaline hydrothermal crystallization method, and then removing carbon to obtain sodalite zeolite molecular sieves. CN105800643A provides a method for preparing 13X molecular sieve by using coal gangue and fly ash desiliconization liquid. The process steps of the present invention include: crushing, grinding and screening the coal gangue, calcining at high temperature for activation pretreatment, and then wet grinding. The slurry after wet grinding is used as an aluminum source and a part of the silicon source, mixed with fly ash desiliconization liquid, and aged, crystallized, filtered, washed and dried in an alkaline environment to obtain 13X molecular sieve. The activation and crystallization process of secondary resources is a key step in synthesizing zeolites, but the current synthesis strategy is mainly based on experience, which often leads to low purity and poor quality of zeolites synthesized from secondary resources.
[0004] Therefore, solving the problem of low purity and poor quality of zeolite synthesized from secondary resources is a difficulty in current research. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide an LSX molecular sieve and a preparation method and application thereof. The present invention uses secondary resources as raw materials, and prepares a high-purity and excellent-quality LSX molecular sieve through thermal activation, alkali melting and crystallization reaction; the preparation method uses secondary resources as raw materials to synthesize LSX molecular sieves, which significantly reduces production costs and solves the problem of secondary resource accumulation, which is of great significance to the environment and economy, has a simple process, and is convenient for industrial production.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing an LSX molecular sieve, the preparation method comprising the following steps:
[0008] (1) thermally activating secondary resources to obtain thermally activated products;
[0009] (2) mixing the thermally activated product and a first alkali source, and performing alkali melting to obtain an alkali melt product;
[0010] (3) mixing the alkali-melted product, a second alkali source and a solvent, and performing a crystallization reaction to obtain the LSX molecular sieve.
[0011] It should be noted that LSX molecular sieve, also known as low silicon-aluminum ratio X-type molecular sieve, has a larger specific surface area and a more negatively charged skeleton, requiring more cations to balance, so it has stronger ion exchange performance and is one of the most commonly used gas separation adsorbents in industry.
[0012] The invention uses secondary resources as raw materials, and prepares a LSX molecular sieve with high purity and excellent quality through thermal activation, alkali melting and crystallization reaction; the preparation method uses secondary resources as raw materials to synthesize LSX molecular sieves, which significantly reduces production costs and solves the problem of accumulation of secondary resources, has important significance for the environment and the economy, has a simple process, and is convenient for industrial production.
[0013] The present invention adds a second alkali source during the crystallization reaction process, which can effectively reduce the silicon-aluminum ratio of the product and improve the purity of the product.
[0014] As a preferred technical solution of the present invention, the secondary resources in step (1) include any one of rare earth tailings, coal gangue or fly ash, or a combination of at least two of them.
[0015] Preferably, the temperature of the thermal activation in step (1) is 600-1400°C, for example, it can be 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C or 1400°C, etc., preferably 1000-1200°C.
[0016] In the present invention, if the temperature of thermal activation is too low, the quartz in the raw material cannot be effectively destroyed and will eventually remain in the product as an impurity, resulting in low product purity; if the temperature of thermal activation is too high, higher requirements are placed on the calcination equipment, and energy consumption increases, which can easily cause unnecessary energy waste.
[0017] Preferably, the thermal activation time in step (1) is 0.5-24 h, for example, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h or 24 h, etc., preferably 0.5-4 h.
[0018] As a preferred technical solution of the present invention, the secondary resources in step (1) are pretreated before thermal activation.
[0019] Preferably, the pretreatment includes crushing and screening.
[0020] The present invention does not specifically limit the method of crushing. Exemplary methods include mechanical crushing, ultrasonic crushing, plasma crushing, or electromagnetic vibration crushing.
[0021] Preferably, the mesh number of the screening is 100-400 mesh, for example, it can be 100 mesh, 110 mesh, 120 mesh, 130 mesh, 140 mesh, 150 mesh, 160 mesh, 170 mesh, 180 mesh, 190 mesh, 200 mesh, 210 mesh, 220 mesh, 230 mesh, 240 mesh, 250 mesh, 300 mesh, 350 mesh or 400 mesh, etc.
[0022] As a preferred technical solution of the present invention, in step (2), the first alkali source includes any one of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate or sodium bicarbonate, or a combination of at least two thereof, preferably sodium hydroxide or sodium carbonate.
[0023] Preferably, the mass ratio of the thermally activated product to the first alkali source in step (2) is 1:(1-1.4), for example, it can be 1:1, 1:1.2, 1:1.3 or 1:1.4, etc., preferably 1:(1.2-1.3).
[0024] The present invention can fully decompose stable components in minerals such as quartz, mullite, etc. within the mass ratio range of 1: (1.2-1.3), and can avoid the problems of sodalite impurity generation or reduced product crystallinity due to excessive alkalinity.
[0025] As a preferred technical solution of the present invention, the mixing time in step (2) is 5-10 minutes, for example, it can be 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes.
[0026] Preferably, grinding is performed during the mixing process in step (2).
[0027] Preferably, the temperature of the alkali melting in step (2) is 350-950°C, for example, 350°C, 450°C, 550°C, 650°C, 750°C, 850°C or 950°C, etc., preferably 450-750°C.
[0028] Preferably, the alkali melting time in step (2) is 0.5-5 h, for example, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, or 5 h, etc., preferably 2-4 h.
[0029] As a preferred technical solution of the present invention, the second alkali source in step (3) includes sodium hydroxide and / or potassium hydroxide, preferably sodium hydroxide and potassium hydroxide.
[0030] Preferably, the mass ratio of sodium hydroxide to potassium hydroxide is (1-7):(1-8), wherein the selection range of sodium hydroxide "1-7" can be, for example, 1, 2, 3, 4, 5, 6 or 7, and the selection range of potassium hydroxide "1-8" can be, for example, 1, 2, 3, 4, 5, 6, 7 or 8, preferably (4-6):(1-6).
[0031] In the present invention, if only sodium hydroxide is used, the product has poor crystallinity and type A zeolite is produced; if only potassium hydroxide is used, the product has poor crystallinity and even zeolite cannot be produced.
[0032] Preferably, the solvent in step (3) comprises water.
[0033] The present invention does not impose any particular limitation on water, and for example, it may be deionized water.
[0034] Preferably, in step (3), the mass ratio of the second alkali source, the solvent and the alkali-melted product is (0.2-1.5):(5-12):1, wherein the selection range of the second alkali source "0.2-1.5" can be, for example, 0.2, 0.3, 0.5, 0.7, 0.9, 1.2 or 1.5, and the selection range of the solvent "5-12" can be, for example, 5, 6, 7, 8, 9, 10, 11 or 12, and is preferably (0.5-1.2)(5-10):1.
[0035] In the present invention, if the mass ratio of the second alkali source to the alkali-melted product is too small, that is, the amount of the second alkali source used is too small, the product purity is low and there are more impurities; if the mass ratio of the second alkali source to the alkali-melted product is too large, that is, the amount of the second alkali source used is too large, a large amount of amorphous material will be generated and the crystallinity will decrease.
[0036] As a preferred technical solution of the present invention, the mixing process in step (3) is accompanied by stirring.
[0037] Preferably, the stirring time is 2-6 h, for example, 2 h, 3 h, 4 h, 5 h or 6 h, etc., preferably 3-5 h.
[0038] Preferably, the temperature of the crystallization reaction in step (3) includes a primary temperature and a secondary temperature.
[0039] The present invention adopts multi-stage temperature to carry out crystallization reaction, which can effectively shorten the crystallization time and improve the crystallinity of the product.
[0040] Preferably, the primary temperature is 25-80°C, for example, it can be 25°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C, etc., preferably 50-80°C.
[0041] Preferably, the insulation time of the primary temperature is 1-6 hours, for example, it can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, etc., preferably 2-5 hours.
[0042] Preferably, the secondary temperature is 100-240°C, for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C, etc., preferably 100-150°C.
[0043] Preferably, the insulation time of the secondary temperature is 1-48h, for example, it can be 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 25h, 30h, 35h, 40h or 48h, etc., preferably 2-18h.
[0044] Preferably, the heating rates of the primary temperature and the secondary temperature are independently 0.5-10°C / min, for example, 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc., preferably 5-7°C / min.
[0045] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0046] (1) crushing and screening the secondary resources, and then thermally activating them at 600-1400° C. for 0.5-24 h to obtain a thermally activated product;
[0047] (2) mixing and grinding the thermally activated product and the first alkali source at a mass ratio of 1:(1-1.4) for 5-10 minutes, and then alkali melting at 350-950° C. for 0.5-5 hours to obtain an alkali-melted product;
[0048] (3) stirring and mixing the second alkali source, the solvent and the alkali-melted product in a mass ratio of (0.2-1.5):(5-12):1, and crystallizing at 25-80° C. for 1-6 h, and at 100-240° C. for 1-48 h, and naturally cooling to room temperature after the crystallization is completed;
[0049] (4) Washing the product obtained in step (3) 1-6 times, and then drying at 60-100° C. for 12-24 hours to obtain the LSX molecular sieve.
[0050] In a second aspect, the present invention provides an LSX molecular sieve, which is prepared by the preparation method described in the first aspect.
[0051] Preferably, the silicon to aluminum atomic ratio of the LSX molecular sieve is less than 1.1, for example, it may be 1.09, 1.08, 1.06, 1.04 or 1.02.
[0052] In a third aspect, the present invention provides a use of the LSX molecular sieve as described in the second aspect, wherein the LSX molecular sieve is used for gas separation.
[0053] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] The invention uses secondary resources as raw materials, and prepares a LSX molecular sieve with high purity and excellent quality through thermal activation, alkali melting and crystallization reaction; the preparation method uses secondary resources as raw materials to synthesize LSX molecular sieves, which significantly reduces production costs and solves the problem of accumulation of secondary resources, has important significance for the environment and the economy, has a simple process, and is convenient for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is the XRD diffraction pattern of the LSX molecular sieve prepared in Example 1 of the present invention.
[0057] Figure 2CO of the LSX molecular sieve prepared in Example 1 of the present invention 2 \CH 4 \N 2 adsorption performance. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0059] The room temperature in the following examples refers to 25°C.
[0060] Example 1
[0061] This embodiment provides a method for preparing LSX molecular sieve, and the secondary resource used is rare earth tailings, and the chemical composition is shown in Table 1.
[0062] Table 1
[0063] Chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[K 2 The]]> NaO CaO other Mass percentage wt.% 41.3 31.1 3.5 8.3 13 1 1.8
[0064] The preparation method comprises the following steps:
[0065] (1) crushing the rare earth tailings and passing them through a 200-mesh sieve, and then thermally activating them at 1200° C. for 3 hours to obtain a thermally activated product;
[0066] (2) mixing and grinding the thermally activated product and sodium hydroxide at a mass ratio of 1:1.2 for 5 minutes, and then placing the ground mixture in a muffle furnace at 550° C. for 3 hours to perform alkali melting to obtain an alkali-melted product;
[0067] (3) a second alkali source, deionized water and the alkali-melted product were stirred and mixed at a mass ratio of 0.9:8:1 for 3 hours, and then the obtained mixture was placed in a stainless steel autoclave lined with polytetrafluoroethylene, crystallized at 70° C. for 3 hours, and crystallized at 100° C. for 16 hours, with a heating rate of 5° C. / min, and naturally cooled to room temperature after the crystallization was completed;
[0068] Wherein, the second alkali source includes potassium hydroxide and sodium hydroxide in a mass ratio of 5:4;
[0069] (4) The product obtained in step (3) was centrifuged and washed four times, and then dried at 90° C. for 12 h to obtain the LSX molecular sieve. Detection by inductively coupled plasma emission spectrometer showed that the silicon-aluminum atomic ratio of the LSX molecular sieve was 1.05.
[0070] Figure 1The XRD diffraction pattern of the LSX molecular sieve prepared in this example is shown. It can be seen from the figure that the XRD diffraction pattern of the LSX molecular sieve has no impurity peaks and is completely consistent with JSPDF: 89-0070.
[0071] Figure 2 The CO of the LSX molecular sieve prepared in this example is shown 2 \CH 4 \N 2 As can be seen from the figure, the carbon dioxide adsorption capacity of the product is much higher than that of methane and nitrogen, and it has significant CO 2 / CH 4 and CO 2 / N 2 Separation performance.
[0072] Example 2
[0073] This embodiment provides a method for preparing LSX molecular sieve, and the secondary resource used is coal gangue, and the chemical composition is shown in Table 2.
[0074] Table 2
[0075] Chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[K 2 The]]> CaO MgO other Mass percentage wt.% 59.3 26.2 5.0 3.4 2.5 1.4 2.2
[0076] The preparation method comprises the following steps:
[0077] (1) crushing the coal gangue and passing it through a 200-mesh sieve, and then thermally activating it at 950° C. for 3 h to obtain a thermally activated product;
[0078] (2) mixing and grinding the thermally activated product and sodium hydroxide at a mass ratio of 1:1.4 for 5 minutes, and then placing the ground mixture in a muffle furnace at 650° C. for 4 hours to perform alkali melting to obtain an alkali-melted product;
[0079] (3) a second alkali source, deionized water and the alkali-melted product were stirred and mixed at a mass ratio of 0.6:8.44:1 for 2 hours, and then the obtained mixture was placed in a stainless steel autoclave lined with polytetrafluoroethylene, crystallized at 50° C. for 5 hours, and crystallized at 120° C. for 10 hours, with a heating rate of 5° C. / min, and naturally cooled to room temperature after the crystallization was completed;
[0080] Wherein, the second alkali source includes potassium hydroxide and sodium hydroxide in a mass ratio of 1:5;
[0081] (4) The product obtained in step (3) was centrifuged and washed 5 times, and then dried at 90° C. for 24 h to obtain the LSX molecular sieve. Detection by inductively coupled plasma emission spectrometer showed that the silicon-aluminum atomic ratio of the LSX molecular sieve was 1.08.
[0082] Example 3
[0083] This embodiment provides a method for preparing LSX molecular sieve, and the secondary resource used is fly ash, and the chemical composition is shown in Table 3.
[0084] Table 3
[0085] Chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[K 2 The]]> CaO MgO other Mass percentage wt.% 55.6 35.2 1.2 1.8 3.1 1.7 1.4
[0086] The preparation method comprises the following steps:
[0087] (1) crushing the fly ash and passing it through a 200-mesh sieve, and then thermally activating it at 1100° C. for 5 h to obtain a thermally activated product;
[0088] (2) mixing and grinding the thermally activated product and sodium hydroxide at a mass ratio of 1:1 for 5 minutes, and then placing the ground mixture in a muffle furnace at 450° C. for 4 hours to perform alkali melting to obtain an alkali-melted product;
[0089] (3) a second alkali source, deionized water and the alkali-melted product were stirred and mixed at a mass ratio of 0.8:8.44:1 for 4 hours, and then the obtained mixture was placed in a stainless steel autoclave lined with polytetrafluoroethylene, crystallized at 70° C. for 3 hours, and crystallized at 100° C. for 8 hours, with a heating rate of 5° C. / min, and naturally cooled to room temperature after the crystallization was completed;
[0090] Wherein, the second alkali source includes potassium hydroxide and sodium hydroxide in a mass ratio of 7:1;
[0091] (4) The product obtained in step (3) was centrifuged and washed 4 times, and then dried at 90° C. for 8 h to obtain the LSX molecular sieve. Detection by inductively coupled plasma emission spectrometer showed that the silicon-aluminum atomic ratio of the LSX molecular sieve was 1.05.
[0092] Example 4
[0093] This embodiment provides a method for preparing LSX molecular sieve, the preparation method comprising the following steps:
[0094] (1) crushing the fly ash and passing it through a 200-mesh sieve, and then thermally activating it at 1400° C. for 2 h to obtain a thermally activated product;
[0095] (2) mixing and grinding the thermally activated product and sodium carbonate at a mass ratio of 1:1.3 for 7 minutes, and then placing the ground mixture in a muffle furnace at 850° C. for 2 hours to perform alkali melting to obtain an alkali-melted product;
[0096] (3) stirring and mixing the second alkali source, deionized water and the alkali-melted product at a mass ratio of 1.5:12:1 for 6 hours, and then placing the obtained mixture into a stainless steel autoclave lined with polytetrafluoroethylene, crystallizing at 30° C. for 6 hours, and at 150° C. for 5 hours, with a heating rate of 7° C. / min, and naturally cooling to room temperature after the crystallization is completed;
[0097] Wherein, the second alkali source includes potassium hydroxide and sodium hydroxide in a mass ratio of 7:8;
[0098] (4) The product obtained in step (3) was centrifuged and washed 6 times, and then dried at 80° C. for 24 h to obtain the LSX molecular sieve. Detection by inductively coupled plasma emission spectrometer showed that the silicon-aluminum atomic ratio of the LSX molecular sieve was 1.08.
[0099] Example 5
[0100] The difference between this embodiment and embodiment 1 is that the temperature of the thermal activation in step (1) is 500°C.
[0101] The rest of the preparation methods and parameters were the same as those in Example 1.
[0102] Example 6
[0103] The difference between this embodiment and embodiment 1 is that the temperature of the thermal activation in step (1) is 1500°C.
[0104] The rest of the preparation methods and parameters were the same as those in Example 1.
[0105] Example 7
[0106] The difference between this embodiment and embodiment 1 is that in step (3), the second alkali source is only potassium hydroxide.
[0107] The rest of the preparation methods and parameters were the same as those in Example 1.
[0108] Example 8
[0109] The difference between this embodiment and embodiment 1 is that in step (3), the second alkali source is only sodium hydroxide.
[0110] The rest of the preparation methods and parameters were the same as those in Example 1.
[0111] Example 9
[0112] The difference between this embodiment and embodiment 1 is that in step (3), the mass ratio of the second alkali source to the alkali-melted product is 0.1:1.
[0113] The rest of the preparation methods and parameters were the same as those in Example 1.
[0114] Example 10
[0115] The difference between this embodiment and embodiment 1 is that in step (3), the mass ratio of the second alkali source to the alkali-melted product is 2:1.
[0116] The rest of the preparation methods and parameters were the same as those in Example 1.
[0117] Embodiment 11
[0118] The difference between this embodiment and embodiment 1 is that the crystallization in step (3) is only carried out at 100° C. for 19 hours.
[0119] The rest of the preparation methods and parameters were the same as those in Example 1.
[0120] Example 12
[0121] The difference between this embodiment and embodiment 1 is that the crystallization in step (3) is only carried out at 70° C. for 19 hours.
[0122] The rest of the preparation methods and parameters were the same as those in Example 1.
[0123] Comparative Example 1
[0124] The difference between this comparative example and Example 1 is that in step (3), no second alkali source is added, but deionized water and the alkali-melted product are directly mixed.
[0125] The rest of the preparation methods and parameters were the same as those in Example 1.
[0126] Performance Testing
[0127] The LSX molecular sieves prepared in Examples 1-12 and Comparative Example 1 were subjected to CO 2 \CH 4 \N 2 Adsorption performance test.
[0128] The test results are shown in Table 1.
[0129] Table 1
[0130]
[0131]
[0132] analyze:
[0133] As can be seen from the above table, the present invention uses secondary resources as raw materials and prepares a high-purity and excellent-quality LSX molecular sieve through thermal activation, alkali melting and crystallization reactions. The molecular sieve has a high carbon dioxide separation performance.
[0134] It can be seen from the data results of Example 1 and Examples 5-6 that if the temperature of thermal activation is too low, it will make it difficult to decompose stable components in the raw materials, such as quartz, and the product has a high impurity content, thereby resulting in low carbon dioxide adsorption and low selectivity; if the temperature of thermal activation is too high, the equipment and energy consumption requirements are too high, the carbon dioxide separation performance is less affected, and it is easy to cause unnecessary energy waste.
[0135] It can be seen from the data results of Example 1 and Examples 7-8 that if only sodium hydroxide is used as the second alkali source, the product crystallinity is poor and type A zeolite is produced; if only potassium hydroxide is used as the second alkali source, the product crystallinity is poor and zeolite cannot even be produced. Both situations will lead to a significant decrease in carbon dioxide separation performance.
[0136] It can be seen from the data results of Example 1 and Examples 9-10 that if the mass ratio of the second alkali source and the alkali-melted product is relatively small, the product purity will decrease, thereby reducing the carbon dioxide separation performance; if the mass ratio of the second alkali source and the alkali-melted product is too large, a large amount of amorphous material will be generated, which will also reduce the carbon dioxide separation performance.
[0137] It can be seen from the data results of Example 1 and Examples 11-12 that if crystallization is performed only at the same temperature, the zeolite crystallinity is poor or the zeolite cannot be synthesized, resulting in a decrease in carbon dioxide separation performance.
[0138] It can be seen from the data results of Example 1 and Comparative Example 1 that if the second alkali source is not added, the zeolite has poor crystallinity and many impurities, which leads to a decrease in carbon dioxide separation performance.
[0139] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing LSX molecular sieve, characterized in that: The preparation method comprises the following steps: (1) thermally activating secondary resources to obtain thermally activated products; (2) mixing the thermally activated product and a first alkali source, and performing alkali melting to obtain an alkali melt product; (3) mixing the alkali-melted product, a second alkali source and a solvent, and performing a crystallization reaction to obtain the LSX molecular sieve.
2. The preparation method according to claim 1, characterized in that: The secondary resources in step (1) include any one of rare earth tailings, coal gangue or fly ash, or a combination of at least two thereof; Preferably, the temperature of the thermal activation in step (1) is 600-1400° C., preferably 1000-1200° C.; Preferably, the thermal activation time in step (1) is 0.5-24 h, preferably 0.5-4 h.
3. The preparation method according to claim 1 or 2, characterized in that: The secondary resource in step (1) is pretreated before thermal activation; Preferably, the pretreatment includes crushing and screening; Preferably, the mesh size of the sieving is 100-400 meshes.
4. The preparation method according to any one of claims 1 to 3, characterized in that Step (2) the first alkali source comprises any one of sodium hydroxide, potassium hydroxide, aqueous ammonia, sodium carbonate or sodium bicarbonate, or a combination of at least two thereof, preferably sodium hydroxide or sodium carbonate; Preferably, the mass ratio of the thermally activated product to the first alkali source in step (2) is 1:(1-1.4), preferably 1:(1.2-1.3).
5. The preparation method according to any one of claims 1 to 4, characterized in that: The mixing time in step (2) is 5-10 minutes; Preferably, grinding is performed during the mixing process in step (2); Preferably, the temperature of the alkali melting in step (2) is 350-950°C, preferably 450-750°C; Preferably, the alkali melting time in step (2) is 0.5-5h, preferably 2-4h.
6. The preparation method according to any one of claims 1 to 5, characterized in that: Step (3) the second alkali source comprises sodium hydroxide and / or potassium hydroxide; Preferably, the mass ratio of sodium hydroxide to potassium hydroxide is (1-7):(1-8), preferably (4-6):(1-6); Preferably, the solvent in step (3) comprises water; Preferably, in step (3), the mass ratio of the second alkali source, the solvent and the alkali-melted product is (0.2-1.5):(5-12):1, preferably (0.5-1.2):(5-10):
1.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The mixing process in step (3) is accompanied by stirring; Preferably, the stirring time is 2-6h, preferably 3-5h; Preferably, the temperature of the crystallization reaction in step (3) includes a primary temperature and a secondary temperature; Preferably, the primary temperature is 25-80°C, preferably 50-80°C; Preferably, the insulation time of the first temperature is 1-6h, preferably 2-5h; Preferably, the secondary temperature is 100-240°C, preferably 100-150°C; Preferably, the insulation time of the secondary temperature is 1-48h, preferably 2-18h; Preferably, the heating rates of the primary temperature and the secondary temperature are independently 0.5-10°C / min, preferably 5-7°C / min.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) crushing and screening the secondary resources, and then thermally activating them at 600-1400° C. for 0.5-24 h to obtain a thermally activated product; (2) mixing and grinding the thermally activated product and the first alkali source at a mass ratio of 1:(1-1.4) for 5-10 minutes, and then alkali melting at 350-950° C. for 0.5-5 hours to obtain an alkali-melted product; (3) stirring and mixing the second alkali source, the solvent and the alkali-melted product in a mass ratio of (0.2-1.5):(5-12):1, and crystallizing at 25-80° C. for 1-6 h, and at 100-240° C. for 1-48 h, and naturally cooling to room temperature after the crystallization is completed; (4) Washing the product obtained in step (3) 1-6 times, and then drying at 60-100° C. for 12-24 hours to obtain the LSX molecular sieve.
9. An LSX molecular sieve, characterized in that The LSX molecular sieve is prepared by the preparation method according to any one of claims 1 to 8; Preferably, the silicon to aluminum atomic ratio of the LSX molecular sieve is less than 1.
1.
10. A use of the LSX molecular sieve according to claim 9, characterized in that: The LSX molecular sieve is used for gas separation.
Citation Information
Patent Citations
Method for preparing 13X molecular sieve by cooperation of coal gangue and coal ash desilication liquid
CN105800643A
A method for synthesizing sodalite zeolite molecular sieves from coal gangue solid waste
CN113307282B